How important are earnings announcements as an information source? - Basu, Sudipta (Institutional Knowledge at Singapore Management University, 2013)
In a competitive information market, no single information source is likely to dominate all other sources collectively, but a single source can dominate all or most other sources individually. We explore whether earnings announcements constitute such a dominant source using Ball and Shivakumar’s R2 metric: the proportion of the variation in annual returns explained by earnings announcement returns. We find that earnings announcement R2 is 11% -- higher than the corresponding R2 of returns on days with dividend announcements, management forecasts, preannouncements, 10-K and 10-Q filings and amendments. Only the four largest realized absolute daily returns in a year match the ability of earnings announcement returns to explain annual returns. We conclude that earnings announcements are the single most important source of new information in the equity market.